Dual regulatory effects of gut microbiota and their metabolites in rheumatoid arthritis: balancing pathogenic and protective mechanisms - Xie, Xingwen; Chen, Xin; Wang, Xuetao; Wang, Sunli; Qi, Peng (Frontiers in Immunology, 2025)
Rheumatoid arthritis is a chronic autoimmune disorder characterized by destructive, symmetric joint inflammation and synovitis, resulting in substantial disability that profoundly compromises patients’ quality of life. Its pathogenesis encompasses complex interactions between genetic and environmental factors. Recent advances in bacterial DNA sequencing technologies have uncovered a significant correlation between the human gut microbiota composition and rheumatoid arthritis progression. Growing clinical and experimental evidence establishes the gut-joint axis as a crucial mediator in rheumatoid arthritis pathogenesis. Comprehensive investigation of gut microbial communities and their metabolites’ influence on rheumatoid arthritis mechanisms, coupled with the elucidation of microbiome’s bidirectional regulatory effects in disease development, not only deepens our understanding of pathological processes but also establishes a theoretical framework for developing novel diagnostic biomarkers and personalized therapeutic interventions to enhance patient outcomes.